6. ETIKA DALAM KEBIJAKAN LUAR NEGERI: KEBIJAKAN ETHIOPIA MENAMPUNG PENGUNGSI PERANG SAUDARA SUDAN SELATAN TAHUN 2013-2015 - Robbani, Saif; Utomo, Tri Cahyo; Rosyidin, Mohammad (Journal of International Relations, 2016)
Ethics is one of the important factors that could affect the pattern of a country's policies.South Sudan civil war occuring in 2013 has enforced its residents to flee to theneighboring countries. Ethiopia, which is a country bordering South Sudan has long had anopen border policy for refugees looking for security. For a developing country, hostingrefugees may provide economic and social burdens, but these burdens do not affectEthiopia to close its borders for refugees. Through Ethiopia’s Refugee Proclamation No.409/2004, Ethiopia with its all limitations has been committed to upholding public interest,that is to continue opening its borders for refugees under any circumstances.